Is the Decline in the Information Content of Earnings Following Restatements Short-Lived? - CHEN, Xia (Institutional Knowledge at Singapore Management University, 2014)
Prior research finds that the decline in the information content of earnings after restatement announcements is short-lived and the earnings response coefficient (ERC) bounces back after three quarters. We re-examine this issue using a more recent and comprehensive sample of restatements. We find that material restatement firms experience a significant decrease in the ERC over a prolonged period—close to three years after restatement announcements. In contrast, other restatement firms experience a decline in the ERC for only one quarter. We further find that among material restatement firms, those that are subject to more credibility concerns and those that do not take prompt actions to improve reporting credibility experience a longer drop in the ERC. Last, reconciling with prior research, we find that using a more powerful proxy for material restatements and imposing less restrictive sampling requirements help to increase the power of the tests to detect the long-run drop in the ERC.